Guanidinium Pairing Facilitates Membrane Translocation - Allolio, Christoph; Baxova, Katarina; Vazdar, Mario; Jungwirth, Pavel (The journal of physical chemistry. B, 2016)
Ab initio free energy calculations of guanidinium pairing in aqueous solution confirm the counterintuitive conjecture that the like-charge ion pair is thermodynamically stable. Transferring the guanidinium pair to the inside of a POPC lipid bilayer, like-charge ion pairing is found to occur also inside the membrane defect. It is found to contribute to the nonadditivity of ion transfer, thereby facilitating the presence of ions inside the bilayer. The effect is quantified by free energy decomposition and comparison with ammonium ions, which do not form a stable pair. The presence of two charges inside the center of the bilayer leads to the formation of a pore. Potential consequences for cell penetrating peptides and ion conduction are drawn.
Keywords: Thermodynamics; Molecular Dynamics Simulation; voda; Phosphatidylcholines; Lipid Bilayers; Guanidine; Water; simulace molekulární dynamiky; lipidové dvojvrstvy; fosfatidylcholiny; kvantová teorie; termodynamika; Quantum Theory; guanidin